(untitled) (Religious dialogue and cooperation, 2025)
This paper is intended to analyse Islamic presence in Modern Greece especially under the perspective of interreligious dialogue between Muslim refugees and Christian majority of Greek population. In this context, many initiatives held by Roman Catholics in Greece, especially Jesuits, Franciscans, local Caritas, Sisters of Mother Theresa, are devoted to Muslim refugees and people of different migratory background. Humanitarian activity promoted by Roman Catholics favours an interactive process with immigrants but also a fight for justice with the result of establishing an interfaith dialogue with Greek Orthodox Christians. The meeting with refugees is aimed not only to give them the possibility of making an income, but also to restore the dignity of migrant people. So, for example, the Jesuit Refugee Center (JRS) and the Jesuit Welcome Center (JWC) are meant to answer the urgent needs of people from Central Asia (Pakistan, Afghanistan), Northern and Sahel Africa (Morocco, Egypt, Somalia, Nigeria) and other countries with Muslim majority. On the other hand, these initiatives favour a regular daily routine through work and/or learning. This goal inspired the “Pedro Arrupe Center”, a social justice and educational project, aimed to help young refugees or children of families with migratory background to better pursue their school integration process.